2001
DOI: 10.1038/85677
|View full text |Cite|
|
Sign up to set email alerts
|

An antisense-based functional genomics approach for identification of genes critical for growth of Candida albicans

Abstract: Converting the complete genome sequence of Candida albicans into meaningful biological information will require comprehensive screens for identifying functional classes of genes. Most systems described so far are not applicable to C. albicans because of its difficulty with mating, its diploid nature, and the lack of functional random insertional mutagenesis methods. We examined artificial gene suppression as a means to identify gene products critical for growth of this pathogen; these represent new antifungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(56 citation statements)
references
References 30 publications
1
53
0
2
Order By: Relevance
“…By combining these multiple diverse data sets, we can construct detailed functional networks, where relationships between genes is established by direct experimental manipulation of their expression. Related efforts using vector-based approaches have already been described for antisense and siRNA for use in either Candida albicans (De Backer et al, 2001) Antisense oligonucleotides are also a valuable technology to suppress gene expression in animals. Like tissue culture studies, the development of the 2 0 -MOEmodified antisense oligonucleotide has been of considerable value in facilitating our ability to generate potent and long-lasting agents to inhibit gene expression in animals.…”
Section: Antisense Oligonucleotide Drug Discovery and Target Validationmentioning
confidence: 99%
“…By combining these multiple diverse data sets, we can construct detailed functional networks, where relationships between genes is established by direct experimental manipulation of their expression. Related efforts using vector-based approaches have already been described for antisense and siRNA for use in either Candida albicans (De Backer et al, 2001) Antisense oligonucleotides are also a valuable technology to suppress gene expression in animals. Like tissue culture studies, the development of the 2 0 -MOEmodified antisense oligonucleotide has been of considerable value in facilitating our ability to generate potent and long-lasting agents to inhibit gene expression in animals.…”
Section: Antisense Oligonucleotide Drug Discovery and Target Validationmentioning
confidence: 99%
“…Such screens represent a massive investment of time and resources, and they are not always feasible. For instance, traditional essentiality screens are difficult in Candida albicans because of its partial-diploid nature, mating differences, and a lack of insertional mutagenesis methods (De Backer et al 2001). Furthermore, recent shotgun sequencing of microbial communities has suggested that <1% of species are amenable to laboratory culture (Riesenfeld et al 2004;Chen and Pachter 2005).…”
mentioning
confidence: 99%
“…HP1 is a mimic of a rRNA sequence in C. albicans that forms quaternary and tertiary contacts in both Escherichia coli (19,28) and Thermus thermophilus (25) ribosomes. 10 200 Ϯ 50 dT 20 600 Ϯ 150 dT 30 500 Ϯ 80 dT 40 650 Ϯ 104 *Intracellular concentrations of 2ЈOMe HP1 at pH 2, 3, 3.5, 4, and 4.5 are 180 Ϯ 60, 100 Ϯ 32, 56 Ϯ 20, 34 Ϯ 7, and 38 Ϯ 10 M, respectively, when the initial OD 540 is 0.01.…”
Section: Resultsmentioning
confidence: 99%
“…The C. albicans genome is being sequenced, and a functional genomics approach has identified essential genes in this organism (10), so the database of targetable sequence is increasing. Biochemical information discovered using related organisms, such as S. cerevisiae, should also facilitate rational design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation